Potential and problems of existing creativity and innovation indices - Hölscher, Michael; Schubert, Julia (Creativity research journal, 2015)
Creativity and innovation are important inputs in the global knowledge economy. However, while the theoretical concepts and the measurement of creativity on the individual level have made considerable progress during the last decades, so-called sectoral approaches to measuring creativity and innovation on the level of aggregate units are less well developed. The article is the first to review and compare the different approaches of the most popular international creativity rankings. Analyzed sectors are countries, companies, and universities. It becomes apparent that company rankings, in particular, are virtually arbitrary, yet different country and university rankings show much higher correlations. Weaknesses in the rankings’ operationalization and modeling of creativity and innovation measures, as well as potential improvements in methodology, are discussed in the context of the current debate in the literature.
Gesehen am 07.09.2020